Bioinformatic characterization of endolysins and holin-like membrane proteins in the lysis cassette of phages that infect Gordonia rubripertincta. - Richard S Pollenz; Jackson Bland; Welkin H Pope (PLoS ONE, 2022)
Holins are bacteriophage-encoded transmembrane proteins that function to control the timing of bacterial lysis event, assist with the destabilization of the membrane proton motive force and in some models, generate large "pores" in the cell membrane to allow the exit of the phage-encoded endolysin so they can access the peptidoglycan components of the cell wall. The lysis mechanism has been rigorously evaluated through biochemical and genetic studies in very few phages, and the results indicate that phages utilize endolysins, holins and accessory proteins to the outer membrane to achieve cell lysis through several distinct operational models. This observation suggests the possibility that phages may evolve novel variations of how the lysis proteins functionally interact in an effort to improve fitness or evade host defenses. To begin to address this hypothesis, the current study utilized a comprehensive bioinformatic approach to systematically identify the proteins encoded by the genes within the lysis cassettes in 16 genetically diverse phages that infect the Gram-positive Gordonia rubripertincta NRLL B-16540 strain. The results show that there is a high level of diversity of the various lysis genes and 16 different genome organizations of the putative lysis cassette, many which have never been described. Thirty-four different genes encoding holin-like proteins were identified as well as a potential holin-major capsid fusion protein. The holin-like proteins contained between 1-4 transmembrane helices, were not shared to a high degree amongst the different phages and are present in the lysis cassette in a wide range of combinations of up to 4 genes in which none are duplicated. Detailed evaluation of the transmembrane domains and predicted membrane topologies of the holin-like proteins show that many have novel structures that have not been previously characterized. These results provide compelling support that there are novel operational lysis models yet to be discovered.